2019
DOI: 10.1111/nmo.13770
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ingestion of deoxynivalenol‐contaminated diet dose‐dependently decreases the area of myenteric neurons and gliocytes of rats

Abstract: Background Deoxynivalenol (DON), a mycotoxin produced by Fusarium spp., is commonly found in cereals ingested by humans and animals. Its ingestion is correlated with hepatic, hematologic, renal, splenic, cardiac, gastrointestinal, and neural damages, according to dose, duration of exposure and species. In this work, the effects of the ingestion of DON‐contaminated diet at concentrations considered tolerable for human and animal intake were assessed. Methods Male Wistar rats aging 21 days were allotted to five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…During a study performed on male Wistar rats ( Rattus novergicus ) aged 21 days, the influence of relatively low doses of DON on the ENS was described [ 14 ]. In that experiment, DON in various doses (from 0.2 mg/kg of chow to 2 mg/kg of chow) was given for 42 days, and the ENS was studied using immunohistochemistry and microscopic analysis.…”
Section: Mycotoxins Affecting the Enteric Neuronsmentioning
confidence: 99%
See 4 more Smart Citations
“…During a study performed on male Wistar rats ( Rattus novergicus ) aged 21 days, the influence of relatively low doses of DON on the ENS was described [ 14 ]. In that experiment, DON in various doses (from 0.2 mg/kg of chow to 2 mg/kg of chow) was given for 42 days, and the ENS was studied using immunohistochemistry and microscopic analysis.…”
Section: Mycotoxins Affecting the Enteric Neuronsmentioning
confidence: 99%
“…In that experiment, DON in various doses (from 0.2 mg/kg of chow to 2 mg/kg of chow) was given for 42 days, and the ENS was studied using immunohistochemistry and microscopic analysis. It was shown that this mycotoxin does not affect the myenteric ganglia organization in the jejunum [ 14 ]. Between control animals and rats receiving DON there were no differences in the density of glial cells located in the myenteric plexus, or the population density of myenteric neurons.…”
Section: Mycotoxins Affecting the Enteric Neuronsmentioning
confidence: 99%
See 3 more Smart Citations